Achieving exceptional strength-ductility synergy in laser beam powder bed fusion René 104ScY superalloy through induced heterogeneous microstructure - Yazhou Zhang; Zuming Liu; Daoyan Jiang; Shupeng Ye; Tao Liu; Runxing Zhou (Journal of Materials Research and Technology)
Balancing strength and ductility presents a significant challenge in the γ′ phase-strengthened Nickel-based superalloys fabricated by laser beam powder bed fusion. This study introduced stable multi-scale heterogeneous microstructure through heat treatment for the first time, which achieves an excellent strength-ductility synergy. The formation mechanism of heterogeneous microstructure during heat treatment and its correlation with mechanical properties are discussed in detail. The results show that the heat treatment leads to the formation of a multi-scale heterogeneous microstructure, including bimodal grains, nano-sized γ′ phases and twins, which activated several strengthening mechanisms, significantly enhancing strength. During the tensile process, stress-induced stacking faults, Lomer-Cottrell locks, and secondary twins activate multiple plastic deformation modes. This effectively improves the work-hardening capacity while maintaining good ductility. The heat treatment process designed in this study achieved a good balance between strength (yield strength: 1281 ± 8 MPa, ultimate tensile strength: 1609 ± 7 MPa) and ductility (16.6 ± 0.3%). These findings propose a new strategy for development of precipitation-strengthened superalloys.